Beyondsoft Co., Ltd. (B) - McFarlan, F. Warren (Franklin Warren); Li, Donghong; Zhang, Hong (Economist) ([London] : SAGE, 2016)
On December 26, 2011, Beyondsoft did its IPO. Its stock was listed on the Small and Medium Enterprise Board of Shenzhen Stock Exchange on January 6, 2012. Raising more than RMB 500 million, the company's net assets soared from RMB 310 million a year earlier to RMB 870 million. In 2010 and 2011, Beyondsoft's sales grew 40.48% and 59.72% respectively, and its total profit growth for the two years was 33.18% and 37.1%. In early 2012, President Ben Wang was pondering: given the rapid development in the past two years, what problems and risks could the company face in the future, and what should its strategy be? This case study aims to answer these questions.
Originally Published in: McFarlan, F. W., Li, D., & Zhang, H. (2012). Beyondsoft Co., Ltd. (B). Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Beyondsoft (Firm); Strategic planning -- Case studies; Business planning -- Case studies; Small business -- Management -- Case studies